The Influence of Perceived Criminal Sanctions and Moral Disengagement on the Intention to Commit Corruption - Misnan Aljawi; Rahmayanti Rahmayanti; Ishak Ali Muda (Universitas Islam Negeri Sumatera Utara, 2026)
Corruption is a crime that has serious impacts on governance and public trust, requiring an approach that integrates both legal and psychological perspectives. This study aims to analyze the effects of perceived criminal sanctions and moral disengagement on the intention to commit corruption. The research employed a quantitative approach with an explanatory research design using a cross-sectional survey. Data were collected through Likert-scale questionnaires measuring perceived criminal sanctions, moral disengagement, and the intention to commit corruption. The research instruments met the validity and reliability criteria, with Cronbach's Alpha values exceeding 0.70. Data were analyzed using descriptive and inferential statistics through multiple linear regression or Structural Equation Modeling (SEM), depending on the characteristics of the data. The findings indicate that perceived criminal sanctions reduce the intention to commit corruption, whereas moral disengagement increases such intentions, and both variables simultaneously have a significant effect on corruptive intentions. This study concludes that corruption prevention should be strengthened through the enhancement of integrity, moral self-regulation, and anti-corruption education supported by a legal psychology approach. The findings are expected to serve as a basis for developing evidence-based corruption prevention policies in Indonesia.